Between knowledge and anxiety: ‘Unveiling the impact of cyberchondria and health literacy on academics’ quality of life in foundation universities - Sert, Kardelen; Altındağ, Erkut; Öngel, Gökten (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of cyberchondria and health literacy on the quality of life of academics working at foundation universities in Türkiye. By examining how excessive online health information seeking and the ability to critically evaluate and utilize this information affect psychological well-being and life satisfaction, the research offers a comprehensive understanding of these dynamics. A quantitative approach was employed, utilizing a structured questionnaire completed by 488 academics. Data were analyzed using SPSS for descriptive statistics and reliability assessments, and SmartPLS for structural equation modeling (SEM) to evaluate the relationships between the variables. The findings reveal a significant negative correlation between cyberchondria and quality of life, while health literacy exerts a positive influence. Moreover, health literacy was found to buffer the detrimental effects of cyberchondria through indirect pathways. These results underscore that cyberchondria may impair well-being by increasing health-related anxiety, whereas health literacy enhances individuals’ capacity to assess health information critically and make informed health decisions. The study concludes that promoting health literacy among academics can serve as a protective factor against the adverse psychological consequences of uncontrolled health information consumption. Institutions are thus encouraged to provide access to reliable digital health resources and offer targeted training programs to strengthen digital health competencies.